استثمار الوسائط الإلكترونية في تعليم النحو العربي: دراسة ميدانية لتلاميذ السنة الأولى متوسط باستخدام الخريطة الذهنية كنموذج مقترحات تطبيقية لنماذج مختارة: Investing in electronic media in teaching Arabic grammar: A field study for first-year students using the mind map as a model applied proposals for selected models - hamidi , Wafa; Issawi , Abdel Salam (Maalim, 2024)
This study aims to reveal the role of electronic media in facilitating the teaching of Arabic grammar in the intermediate education stage, through the adoption of the mind map as an educational model. The study seeks to analyze the impact of the use of this method on the acquisition of language and grammatical skills by learners, in addition to studying its psychological and cognitive implications on students. The preliminary results showed that investing the mind map through electronic media contributes to improving grammatical understanding among learners, with varying effects on performance between classrooms. Despite the high expectations for positive results, some challenges still face the optimal use of these methods.